1990
DOI: 10.1152/ajprenal.1990.258.2.f254
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and renal actions of endothelin: effects of calcium-channel blockers

Abstract: We have evaluated the effects of two calcium-channel blockers, verapamil (VP) and manganese (Mn), on endothelin (EN)-induced changes in systemic and renal function in pentobarbital sodium-anesthetized female rats and male and female dogs. In the rat studies, saline was infused at 24 microliters/min iv with or without (n = 10) two doses of VP (0.02 mg.kg-1.min-1, n = 5; 0.03 mg.kg-1.min-1, n = 3) or Mn (0.5 mg.kg-1.min-1, n = 5) throughout the entire experiment. After surgery, rats were allowed 60 min to stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…17,19,20,23,24 The current study represents our initial investigation into the calcium signaling mechanisms in preglomerular vascular smooth muscle cells and reveals signaling pathways similar to those previously described in largecaliber arteries, cultured vascular smooth muscle cells, and endothelial cells. 1,15,17,20,25 In nonrenal vascular smooth muscle, endothelin evokes a biphasic elevation of [Ca 2ϩ ] i by binding to ET A receptors at the cell surface and activating a pertussis toxin-insensitive G-protein that in turn stimulates phospholipase C (PLC).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…17,19,20,23,24 The current study represents our initial investigation into the calcium signaling mechanisms in preglomerular vascular smooth muscle cells and reveals signaling pathways similar to those previously described in largecaliber arteries, cultured vascular smooth muscle cells, and endothelial cells. 1,15,17,20,25 In nonrenal vascular smooth muscle, endothelin evokes a biphasic elevation of [Ca 2ϩ ] i by binding to ET A receptors at the cell surface and activating a pertussis toxin-insensitive G-protein that in turn stimulates phospholipase C (PLC).…”
Section: Discussionsupporting
confidence: 60%
“…However, in the renal circulation, evidence suggests the presence of both ET A and ET B receptors that produce vasoconstriction. 7,8,15,20,22,23 To date, there are only limited data demonstrating the functional distribution of ET A and ET B receptors along preglomerular resistance vessels. Endlich et al, 6 using the split hydronephrotic kidney technique, reported that ET B receptor-mediated vasoconstriction was present at both preglomerular and postglomerular sites, whereas ET A receptors are strictly preglomerular.…”
Section: Discussionmentioning
confidence: 99%
“…5-11 ET-1 is a peptide produced by endothelial cells that acts as a vasoconstrictor in most vascular beds, including the renal vasculature. 15,16 Its concentration in the plasma presumably reflects a spillover from local release minus that which is removed from the circulation, and thus is an indirect cumulative measure of release from individual vascular beds. The elevated plasma ET-1 may result from a decreased renal clearance with impaired excretion or metabolism for ET-1, as is the case for many other peptide hormones in chronic renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…Verapamil has been shown to counteract the effects of ET on the heart but less so on the kidney in animal studies. 89,90 Nevertheless, verapamil and the dihydropyridine nifedipine constitute potent tools to inhibit endothelin-induced vasoconstriction. These are highly effective agents for abolishing the actions of an endothelin infusion on the kidney in healthy human volunteers, 57,91 as well as in patients with chronic hypertension.…”
Section: Endothelin and Diseasementioning
confidence: 99%